Solution to Singular Optimal Control by Backward Differential Flow - Jinghao Zhu; Shangrui Zhao; Guohua Liu (Journal of Control Science and Engineering)
This paper presents a backward differential flow for solving singular optimal control problems. By using Krotov equivalent transformation, the cost functional is converted to a class of global optimization problems. Some properties of the flow are given to reveal the significant relationship between the dynamic of the flow and the geometry of the feasible set. The proposed method is also used in solving a class of variational problems. Some examples are illustrated.